An Integrated Microrobotic Platform for On‐Demand, Targeted Therapeutic Interventions. (4th November 2013) - Fusco, Stefano; Sakar, Mahmut Selman; Kennedy, Stephen; Peters, Christian; Bottani, Rocco; Starsich, Fabian; Mao, Angelo; Sotiriou, Georgios A.; Pané, Salvador; Pratsinis, Sotiris E.; Mooney, David; Nelson, Bradley J.
<x xml:space="preserve">Abstract</x> The presented microrobotic platform combines together the advantages of self‐folding NIR light sensitive polymer bilayers, magnetic alginate microbeads, and a 3D manipulation system, to propose a solution for targeted, on‐demand drug and cell delivery. First feasibility studies are presented together with the potential of the full design. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>